Polarizing plate, polarizing plate with phase difference layer, and organic electroluminescent display device

By providing a protective layer with high moisture permeability and low iodine adsorption on the polarizer of the organic EL display device and thinning the adhesive layer, the problem of easy decolorization of the polarizer is solved, and the stability and display effect in the organic EL display device are improved.

CN116097333BActive Publication Date: 2025-04-18NITTO DENKO CORP
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202180054139.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-02
Filing Date
2021-07-19
Publication Date
2025-04-18
Estimated Expiration
2041-07-19

AI Technical Summary

Technical Problem

In the prior art, the circular polarizer used in the organic EL display device is prone to decolorization, mainly due to ammonia generated by the organic EL panel.

Method used

By providing a protective layer on the visual identification side of the polarizing plate, the thickness of the adhesive layer is set to be 0.5 μm or less, the moisture permeability of the protective layer is set to be 200 g/m2·24h or more, and the iodine adsorption amount per unit area is set to be 0.01 mg/cm2 or less, so as to block and discharge ammonium ions, and significantly suppress decolorization of the polarizing plate.

Benefits of technology

The decolorization of the polarizing plate in the organic EL display device is effectively suppressed, ensuring the stability and display effect of the polarizing plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116097333B_ABST
    Figure CN116097333B_ABST
Patent Text Reader

Abstract

Provided are a polarizing plate and a polarizing plate with a phase difference layer in which discoloration is significantly suppressed when applied to an organic EL display device. The polarizing plate of an embodiment of the present invention comprises: a polarizer, and a protective layer attached to the visual recognition side of the polarizer via an adhesive layer. The thickness of the adhesive layer is less than 0.5 μm, and the moisture permeability of the protective layer is 200 g / m 2 More than 24 hours, and the iodine adsorption per unit area is 0.01mg / cm 2 The adhesive layer is typically composed of an aqueous adhesive containing a polyvinyl alcohol-based resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing plate, a polarizing plate with a phase difference layer, and an organic electroluminescent (EL) display device. Background Art

[0002] In recent years, with the popularity of thin displays, displays equipped with organic EL panels (organic EL display devices) have been proposed. Since the organic EL panel has a highly reflective metal layer, it is easy to cause problems such as external light reflection and background reflection. Therefore, it is known to prevent these problems by providing a circular polarizer on the visual recognition side (for example, patent documents 1 to 3). However, the circular polarizer provided in the organic EL display device (in fact, the polarizer contained in the circular polarizer) has the problem of easy discoloration.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2003-311239

[0006] Patent Document 2: Japanese Patent Application Publication No. 2002-372622

[0007] Patent Document 3: Japanese Patent No. 3325560 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide a polarizing plate and a polarizing plate with a retardation layer in which discoloration is significantly suppressed when used in an organic EL display device.

[0010] Solutions for solving problems

[0011] The polarizing plate of the embodiment of the present invention comprises: a polarizer, and a protective layer attached to the visual recognition side of the polarizer via an adhesive layer. The thickness of the adhesive layer is less than 0.5 μm, and the moisture permeability of the protective layer is 200 g / m 2 More than 24 hours, and the iodine adsorption per unit area is 0.01mg / cm 2 the following.

[0012] In one embodiment, the polarizer has a cross absorbance A at a wavelength of 550 nm. 550 Orthogonal absorbance A at wavelength 210nm 210 The ratio (A 550 / A 210 ) is 1.4 or more, and the orthogonal absorbance A at a wavelength of 470nm 470 Orthogonal absorbance A at wavelength 600nm600 The ratio (A 470 / A 600 ) is greater than 0.7, and the orthogonal b value is greater than -10.

[0013] In one embodiment, the adhesive layer is composed of a water-based adhesive. In one embodiment, the water-based adhesive contains a polyvinyl alcohol-based resin.

[0014] In one embodiment, the iodine concentration of the polarizer is 4 wt % to 10 wt %.

[0015] In one embodiment, when the polarizing plate is exposed to ammonia vapor at 60° C. for 2 hours, an absolute value |ΔP| of a change in polarization degree is 50% or less.

[0016] According to another aspect of the present invention, a polarizing plate with a phase difference layer is provided, wherein the polarizing plate with a phase difference layer comprises the above polarizing plate and a phase difference layer.

[0017] According to another aspect of the present invention, an organic electroluminescent display device is provided, wherein the organic electroluminescent display device comprises the above-mentioned polarizing plate or the above-mentioned polarizing plate with a phase difference layer.

[0018] Effects of the Invention

[0019] According to the embodiment of the present invention, the thickness of the adhesive layer adjacent to the polarizer is set to 0.5 μm or less, and the moisture permeability of the protective layer on the visual recognition side of the polarizer is set to 200 g / m 2 ·24 hours or more and the iodine adsorption per unit area is set to 0.01 mg / cm 2 As described below, it is possible to realize a polarizing plate and a polarizing plate with a retardation layer in which discoloration is significantly suppressed when applied to an organic EL display device. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. DETAILED DESCRIPTION

[0021] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0022] A.Polarizing plate

[0023] A-1. Overall structure of polarizing plate

[0024] Figure 1This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. The polarizing plate 100 shown in the figure includes: a polarizer 10, and a protective layer (visual recognition side protective layer) 30 bonded to the visual recognition side of the polarizer 10 by means of an adhesive layer 20. The adhesive layer 20 is preferably composed of an aqueous adhesive. The aqueous adhesive preferably contains a polyvinyl alcohol (PVA) resin. In practice, an adhesive layer 40 is provided on the side of the polarizer 10 opposite to the visual recognition side. Typically, an optical functional layer can be bonded by means of the adhesive layer 40. As representative examples of optical functional layers, another protective layer (inner protective layer) and a phase difference layer can be cited. Preferably, the inner protective layer can be omitted. When the optical functional layer is a phase difference layer, a polarizing plate with a phase difference layer can be formed. The polarizing plate with a phase difference layer will be described in Item B below. The polarizing plate 100 can also be bonded to an organic EL panel by means of an adhesive layer 40.

[0025] In the embodiment of the present invention, the thickness of the adhesive layer 20 is 0.5 μm or less, and the moisture permeability of the visual recognition side protection layer 30 is 200 g / m 2 · More than 24 hours and the iodine adsorption per unit area is 0.01 mg / cm 2Below. When the present inventors applied the polarizing plate and the polarizing plate with phase difference layer to the organic EL display device, they encountered the new problem of discoloration of the polarizing plate and the polarizing plate with phase difference layer. The problem was studied in depth, and it was found that the cause of discoloration was ammonia (substantially ammonium ions) produced by the organic EL panel. Furthermore, the means for suppressing the discoloration caused by ammonia were studied in depth, and it was found that by blocking the ammonium ions invading the polarizer as much as possible, and discharging the ammonium ions that have invaded as much as possible, the discoloration can be significantly suppressed. Based on such insights, it was found that by thinning the thickness of the adhesive that the polarizer and the visual recognition side protective layer are bonded as much as possible, and setting the moisture permeability of the visual recognition side protective layer to more than a specified value and setting the iodine adsorption amount to less than a specified value, the ammonium ions that invaded the polarizer can be easily discharged, solving the new problem. Furthermore, by thinning the layer (adhesive layer) adjacent to the polarizer, the iodine adsorption amount of the adjacent layer becomes smaller, and the adsorption of iodine from the polarizer can be suppressed. As a result, discoloration can be suppressed by the synergistic effect with the effect of setting the iodine adsorption amount of the visual recognition side protective layer to below the specified value. In addition, the ammonium ions discharged from the adhesive layer (substantially moved to the visual recognition side protective layer) escape due to the large moisture permeability of the visual recognition side protective layer, and are not captured by the visual recognition side protective layer, and are discharged to the outside of the polarizing plate. As described above, the ammonium ions that invade the polarizer from the organic EL panel can be well discharged to the outside of the polarizing plate. Therefore, when the polarizing plate and the polarizing plate with a phase difference layer are applied to an organic EL display device, discoloration can be well suppressed. It should be noted that the main purpose of the protective layer of the polarizer is to protect the polarizer from moisture (water vapor) damage, and is therefore designed to reduce the moisture permeability of the protective layer on the outside (visual recognition side), but the embodiment of the present invention is based on an embodiment of a technical idea that is completely opposite to the technical common sense in this field.

[0026] The thickness of the adhesive layer is as described above 0.5 μm or less, preferably 0.2 μm or less, more preferably 0.1 μm or less, further preferably 0.08 μm or less, and particularly preferably 0.06 μm or less. On the other hand, the thickness of the adhesive layer is, for example, 0.01 μm or more, and for example, 0.02 μm or more, and for example, 0.03 μm or more. The thinner the thickness of the adhesive layer, the more preferred, but on the other hand, if the thickness is too thin, the layer itself may not be formed sometimes, and bubbles may be generated sometimes. When the thickness of the adhesive layer is in such a range, a layer that can function as an adhesive layer may be formed, and ammonium ions may be discharged well.

[0027] The moisture permeability of the visual recognition side protective layer is 200 g / m 2 24h or more, preferably 300g / m 2 24h or more, more preferably 330g / m 224h or more, more preferably 360g / m 2 24h or more, particularly preferably 400g / m 2 24 hours or more. The upper limit of the moisture permeability of the visual recognition side protective layer can be, for example, 1000 g / m 2 · 24h. When the moisture permeability of the visual recognition side protective layer is within such a range, an appropriate balance between protection of the polarizer and discharge of ammonium ions can be achieved. It should be noted that the moisture permeability can be measured in accordance with JIS Z0208.

[0028] The iodine adsorption amount per unit area of ​​the visual recognition side protective layer is 0.01 mg / cm as described above. 2 Below, preferably 0.005 mg / cm 2 As follows. When the iodine adsorption amount of the visual recognition side protective layer is within such a range, the iodine adsorption from the polarizer can be suppressed, and as a result, discoloration can be suppressed. The iodine adsorption amount can be adjusted by appropriately setting the type of constituent material of the visual recognition side protective layer, the thickness of the visual recognition side protective layer, etc. The iodine adsorption amount is obtained, for example, based on the iodine detection intensity (kcps) obtained by a scanning fluorescent X-ray analyzer and the standard curve of the measuring device. The standard curve can be made by measuring known test materials. A more detailed measurement method is as follows. A specified amount of iodine aqueous solution of a specified concentration is placed in a glass bottle of a specified capacity. The measurement sample (visual recognition side protective layer) is installed on the inner side of the lid of the glass bottle, and the glass bottle is sealed with the lid to form a state in which the measurement sample is suspended inside the sealed glass bottle. The lower end of the measurement sample is separated from the liquid surface of the iodine aqueous solution by an appropriate distance (for example, about tens of mm). In this state, the glass bottle is heated at a specified temperature for a specified time. After heating, the sample was taken out and the iodine detection intensity (kcps) was measured using a scanning fluorescent X-ray analyzer (Rigaku Co., Ltd., "ZSXPrimus IV"). The iodine adsorption amount (mg) was calculated using the calibration curve of the measuring device, and the iodine adsorption amount was divided by the volume (cm 3 ), calculate the iodine adsorption per unit volume (volume iodine adsorption: unit: mg / cm 3 It should be noted that the volume iodine adsorption is a value inherent to the material. The iodine adsorption per unit area (area iodine adsorption: unit mg / cm 2 ). It should be noted that the standard curve of the measuring device is as follows, for example. This standard curve is prepared by measuring a known test material.

[0029] Iodine mass (μg) = iodine detection strength (kcps) × 13.525

[0030] The absolute value of the change in polarization degree when the polarizing plate is exposed to ammonia vapor for 2 hours at 60°C |ΔP| is preferably 50% or less, more preferably 25% or less, and further preferably 10% or less. The smaller |ΔP| is, the better, and ideally zero. According to an embodiment of the present invention, by adopting the structure as described above, the intrusion of ammonium ions into the polarizer can be well suppressed, and the ammonium ions can be well discharged from the polarizer. As a result, even if the polarizing plate is exposed to ammonia, the change in polarization degree (substantially the decrease in polarization degree) is significantly suppressed. When such a polarizing plate (resulting in a polarizing plate with a phase difference layer) is applied to an organic EL display device, discoloration can be well suppressed.

[0031] Hereinafter, the polarizer, the adhesive layer, the protective layer, and the pressure-sensitive adhesive layer will be described in detail.

[0032] A-2. Polarizer

[0033] The polarizer 10 is typically made of a PVA-based resin film containing a dichroic substance (typically iodine).

[0034] Polarizer preferably has an orthogonal absorbance A at a wavelength of 550nm 550 Orthogonal absorbance A at wavelength 210nm 210 The ratio (A 550 / A 210 ) is 1.4 or more, and the orthogonal absorbance A at a wavelength of 470nm 470 Orthogonal absorbance A at wavelength 600nm 600 The ratio (A 470 / A 600 ) is 0.7 or more, and the orthogonal b value is greater than -10. The polarizer used in the embodiment of the present invention is compared with a conventional thin polarizer. 550 / A 210 ) and (A 470 / A 600 ) is very large. This means that the content ratio of iodine ions (having absorption in the ultraviolet region around 210nm) that do not form a complex with PVA in the polarizer is very small, and the content ratio of PVA-iodine complex (having absorption in the visible light region) is very large. More specifically, the content ratio of PVA-I5 having absorption around 600nm in the polarizer is - The complex contains a very large amount of PVA-I3, which absorbs at around 480nm. -The content ratio of the complex is maintained without being significantly reduced. Here, the thickness of the polarizer refers to the length of the optical path, so when the thickness of the polarizer is simply reduced, the optical path also becomes shorter and the polarization performance is also reduced. The amount of iodine that can be contained in the polarizer is also limited, so in order to achieve both high polarization performance and thin polarizer, the iodine contained in the polarizer must be effectively utilized. That is, by reducing the iodine ions that absorb light in the ultraviolet but do not contribute to the polarization performance and increasing the ratio of PVA-iodine complexes that absorb light in the visible light region, it is possible to achieve both high polarization performance and thin polarizer. In other words, by increasing the ratio (A 550 / A 210 ), it is possible to achieve thin and high optical properties. 470 / A 600 ) is maintained above the specified value, and good polarization performance can be achieved in the entire visible light region. When the amount of iodine in a thin polarizer is limited, it is difficult to increase the ratio (A) by relying on conventional technology. 550 / A 210 ) and ratio (A 470 / A 600 ) both, but the polarizer used in the embodiment of the present invention can increase the above two. 550 / A 210 ) is preferably 1.8 or more, more preferably 2.0 or more, and still more preferably 2.2 or more. 550 / A 210 The upper limit of ) can be, for example, 3.5. 470 / A 600 ) is preferably 0.75 or more, more preferably 0.80 or more, and still more preferably 0.85 or more. 470 / A 600 ) is, for example, 2.00, preferably 1.33. It should be noted that the orthogonal absorbance can be obtained by the following formula based on the orthogonal transmittance Tc measured when obtaining the polarization degree described later.

[0035] Orthogonal absorbance = log10(100 / Tc)

[0036] Furthermore, the orthogonal b value of the polarizer is greater than -10, preferably greater than -7, and more preferably greater than -5, as described above. The upper limit of the orthogonal b value is preferably less than +10, and more preferably less than +5. According to the present invention, such a range of orthogonal b values ​​can be achieved. The orthogonal b value represents the hue when the polarizer (polarizer) is configured in an orthogonal state. The larger the absolute value of the value, the more the orthogonal hue (black display of the image display device) looks to be toned. For example, when the orthogonal b value is as low as less than -10, the black display looks blue and the display performance is reduced. That is, according to an embodiment of the present invention, a polarizer that can achieve excellent hue in black display can be obtained. It should be noted that the orthogonal b value can be measured using a spectrophotometer represented by LPF200.

[0037] The polarizer preferably shows absorption dichroism at any wavelength in the wavelength range of 380nm to 780nm. The monomer transmittance of the polarizer is preferably 46.0% or less, more preferably 45.0% or less. On the other hand, the monomer transmittance is preferably 41.5% or more, more preferably 42.0% or more, and further preferably 42.5% or more. The polarization degree of the polarizer is preferably 99.990% or more, preferably 99.998% or less. The polarizer used in the embodiment of the present invention can take into account both high monomer transmittance and high polarization degree. The above monomer transmittance is representatively the Y value measured using an ultraviolet visible spectrophotometer and corrected for visual sensitivity. In addition, the monomer transmittance is the value when the refractive index of one surface of the polarizing plate is converted to 1.50 and the refractive index of the other surface is converted to 1.53. The above polarization degree is representatively obtained by the following formula based on the parallel transmittance Tp and the orthogonal transmittance Tc measured using an ultraviolet visible spectrophotometer and corrected for visual sensitivity.

[0038] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0039] The thickness of the polarizer is preferably 15 μm or less, more preferably 12 μm or less, further preferably 10 μm or less, and particularly preferably 8 μm or less. On the other hand, the thickness of the polarizer is, for example, 1 μm or more, for example, 2 μm or more, and for example, 3 μm or more. When the thickness of the polarizer is within such a range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.

[0040] The iodine concentration of the polarizer is 4 wt% to 10 wt%, more preferably 5 wt% to 8 wt%. When the iodine concentration of the polarizer is within this range, the iodine concentration is high and the polyiodide ion (I3 - 、I5 -) interacts strongly with PVA and exists more stably, so it is not easy to decolorize. In this specification, "iodine concentration" refers to the amount of all iodine contained in the polarizer (PVA-based resin film). More specifically, in the polarizer, iodine is present in the form of iodide ions (I - ), iodine molecules (I2), polyiodide ions (I3 - 、I5 - ) and other forms, the iodine content in this specification refers to the amount of iodine including all these forms. The iodine concentration can be calculated, for example, using a standard curve method of fluorescent X-ray analysis.

[0041] The boric acid concentration of the polarizer is preferably 15 wt % or more, more preferably 16 wt % or more, and further preferably 16 wt % to 26 wt %. When the boric acid concentration of the polarizer is within such a range, practical optical properties can be obtained, and the intrusion of ammonium ions into the polarizer can be suppressed. Furthermore, the ease of curl adjustment during lamination can be well maintained, the curl during heating can be well suppressed, and the durability of the appearance during humidification can be improved. The boric acid concentration can be determined, for example, using Fourier transform infrared spectroscopy (FT-IR). Specifically as follows. For the second PVA-based resin layer, a Fourier transform infrared spectrophotometer (for example, manufactured by Perkin Elmer, trade name "SPECTRUM2000") is used to measure the boric acid peak (665cm -1 ) intensity and the reference peak (2941cm -1 ) intensity. The boric acid amount index is calculated according to the obtained boric acid peak intensity and the reference peak intensity by the following formula, and further, the boric acid concentration can be calculated according to the calculated boric acid amount index by the following formula.

[0042] (boric acid index) = (boric acid peak 665cm -1 The intensity of the reference peak is 2941cm -1 Strength)

[0043] (boric acid concentration) = (boric acid index) × 6.61 + 0.47

[0044] The resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.

[0045] Specific examples of polarizers composed of a single-layer resin film include: polyvinyl alcohol (PVA) films, partially formalized PVA films, ethylene-vinyl acetate copolymer partially saponified films, etc., which are dyed and stretched with dichroic substances such as iodine and dichroic dyes; polyene-based oriented films such as dehydrated PVA and dehydrochlorinated polyvinyl chloride films, etc. From the perspective of excellent optical properties, it is preferred to use a polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it.

[0046] The above-mentioned iodine-based dyeing is carried out, for example, by immersing the PVA film in an iodine aqueous solution. The stretching ratio of the above-mentioned uniaxial stretching is preferably 3 to 7 times. The stretching can be carried out after the dyeing treatment, or it can be carried out while dyeing. In addition, it can also be dyed after stretching. As needed, the PVA film is subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. For example, by immersing the PVA film in water for washing before dyeing, not only can the stains and anti-blocking agents on the surface of the PVA film be cleaned, but also the PVA film can be swollen to prevent uneven dyeing.

[0047] As a specific example of a polarizer obtained using a laminate, there can be cited: a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate; or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be made, for example, as follows: a PVA-based resin solution is applied to a resin substrate, dried to form a PVA-based resin layer on the resin substrate, and a laminate of the resin substrate and the PVA-based resin layer is obtained; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. Stretching typically includes immersing the laminate in a boric acid aqueous solution for stretching. Furthermore, stretching may also include stretching the laminate in the air at a high temperature (for example, above 95°C) before stretching in a boric acid aqueous solution as required. Moreover, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment, wherein the drying shrinkage treatment is to heat the laminate while conveying the laminate in the length direction, thereby shrinking it by more than 2% in the width direction. Representatively, the manufacturing method of the present embodiment includes sequentially applying an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment to the laminate. By introducing auxiliary stretching, the crystallinity of PVA can be improved even when PVA is coated on a thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of PVA in advance, it is possible to prevent problems such as a decrease in orientation and dissolution of PVA when immersed in water in subsequent dyeing and stretching processes, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the polyvinyl alcohol molecules and the decrease in orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. Thus, the optical properties of the polarizer obtained by the treatment process of immersing the laminate in a liquid such as a dyeing treatment and an underwater stretching treatment can be improved. Furthermore, by drying and shrinking the laminate in the width direction, the optical properties can be improved. The obtained laminate of the resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of the polarizer), or the resin substrate can be peeled off from the laminate of the resin substrate / polarizer, and any appropriate protective layer that meets the purpose can be stacked on the peeling surface for use. The details of the manufacturing method of such a polarizer are, for example, recorded in Japanese Patent Publication No. 2012-73580 and Japanese Characteristic No. 6470455. The entire records of these publications are cited in this specification as a reference.

[0048] A-3. Adhesive layer

[0049] The adhesive layer is typically composed of an aqueous adhesive as described above. The aqueous adhesive preferably contains a PVA resin as described above. The adhesive layer can be typically formed by applying an aqueous solution of a PVA resin and drying it. The average degree of polymerization of the PVA resin contained in the aqueous solution is preferably about 100 to 5000, and more preferably 1000 to 4000. The average degree of saponification is preferably about 85 mol% to 100 mol%, and more preferably 90 mol% to 100 mol%. When the average degree of polymerization and the average degree of saponification are in such a range, the adhesion to the polarizer is excellent, and as a result, the adverse effect on the discharge of ammonium ions at the interface with the polarizer can be prevented. As a result, when a polarizing plate and a polarizing plate with a phase difference layer are applied to an organic EL display device, discoloration can be better suppressed.

[0050] The PVA resin preferably contains acetoacetyl groups. This is because the polarizer has excellent adhesion to the protective layer and excellent durability. The PVA resin containing acetoacetyl groups is obtained, for example, by reacting the PVA resin with diketene by any method. The acetoacetyl modification degree of the PVA resin containing acetoacetyl groups is typically 0.1 mol% or more, preferably about 0.1 mol% to 40 mol%, more preferably 1 mol% to 20 mol%, and particularly preferably 2 mol% to 7 mol%. It should be noted that the acetoacetyl modification degree is a value measured by NMR.

[0051] The resin concentration in the PVA-based resin aqueous solution is preferably 0.1 to 15% by weight, more preferably 0.5 to 10% by weight. The viscosity of the aqueous solution is preferably 1 to 50 mPa·s. The pH of the aqueous solution is preferably 2 to 6, more preferably 2.5 to 5, further preferably 3 to 5, and particularly preferably 3.5 to 4.5.

[0052] The PVA-based resin aqueous solution (and thus the adhesive layer) may contain a metal compound colloid in one embodiment. The metal compound colloid is a substance in which metal compound particles are dispersed in a dispersion medium, and the particles are electrostatically stabilized due to mutual repulsion of like charges, and thus have long-term stability.

[0053] The average particle size of the particles forming the metal compound colloid can be set to any appropriate value as long as it does not adversely affect the optical properties such as transparency and polarization properties. It is preferably 1 nm to 100 nm, and more preferably 1 nm to 50 nm. This is because the particles can be evenly dispersed in the adhesive layer.

[0054] As the metal compound, any appropriate compound can be used. For example, metal oxides such as aluminum oxide, silicon dioxide, zirconium oxide, and titanium oxide; metal salts such as aluminum silicate, calcium carbonate, magnesium silicate, zinc carbonate, barium carbonate, and calcium phosphate; and minerals such as cerium silicate, talc, clay, and kaolin. It is preferred to use a metal compound colloid having a positive charge. As the metal compound, aluminum oxide, titanium oxide, and the like can be mentioned, and aluminum oxide is particularly preferred.

[0055] A-4. Protective layer

[0056] The visual recognition side protective layer 30 and the inner protective layer (if present) are respectively formed by any appropriate film that can be used as a protective layer of a polarizer. For specific examples of the material as the main component of the film, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyether sulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, (meth) acrylic resins, acetate resins, etc. can be cited. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic resins, carbamate resins, (meth) acrylic carbamate resins, epoxy resins, silicone resins, etc. can also be cited. In addition, for example, glassy polymers such as siloxane polymers can also be cited. In addition, polymer films described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition having an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be mentioned. The polymer film can be, for example, an extrusion molding of the above-mentioned resin composition.

[0057] The moisture permeability of the visual-viewing-side protective layer is as described in the above section A-1. The visual-viewing-side protective layer having such a moisture permeability may preferably be composed of a TAC film.

[0058] The visual recognition side protective layer can be subjected to surface treatments such as hard coating, anti-reflection treatment, anti-adhesion treatment, and anti-glare treatment as needed. And / or, the visual recognition side protective layer can be subjected to a treatment for improving the visual recognition in the case of visual recognition through polarized sunglasses as needed (representatively, imparting (elliptical) circular polarization function and imparting ultra-high phase difference). By implementing such a treatment, even in the case of visual recognition of the display screen through polarized lenses such as polarized sunglasses, excellent visual recognition can be achieved. Therefore, polarizing plates and polarizing plates with phase difference layers can also be suitably applied to image display devices that can be used outdoors.

[0059] The thickness of the visual side protection layer 30 is preferably 10 μm to 60 μm, more preferably 15 μm to 50 μm. When the surface treatment is applied, the thickness of the visual side protection layer 30 is the thickness including the thickness of the surface treatment layer.

[0060] The inner protective layer (if present) is preferably optically isotropic in one embodiment. In this specification, "optically isotropic" means that the in-plane phase difference Re (550) is 0nm to 10nm, and the phase difference Rth (550) in the thickness direction is -10nm to +10nm. The thickness of the other protective layer is preferably 5μm to 80μm, more preferably 10μm to 40μm, and further preferably 10μm to 30μm. In the embodiment of the present invention, the inner protective layer is preferably omitted.

[0061] A-5. Adhesive layer

[0062] As the adhesive constituting the adhesive layer, representative examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, quantity, combination and blending ratio of the monomers of the base resin forming the adhesive, as well as the blending amount, reaction temperature, reaction time, etc. of the crosslinking agent, an adhesive having desired properties that meet the purpose can be prepared. The base resin of the adhesive can be used alone or in combination with more than two kinds. From the viewpoints of transparency, processability and durability, acrylic adhesives (acrylic adhesive compositions) are preferred. Acrylic adhesive compositions are representative of containing (methyl) acrylic polymers as the main component. (Meth) acrylic polymers can be included in the adhesive composition in a ratio of, for example, more than 50% by weight, preferably more than 70% by weight, and more preferably more than 90% by weight in the solid content of the adhesive composition. (Meth) acrylic polymers contain (methyl) alkyl acrylate as the main component in the form of monomer units. It should be noted that (methyl) acrylate refers to acrylate and / or methacrylate. The (meth)acrylic acid alkyl ester can be contained in the monomer component forming the (meth)acrylic acid polymer in a proportion of preferably 80% by weight or more, more preferably 90% by weight or more. As the alkyl group of the (meth)acrylic acid alkyl ester, for example, a linear or branched alkyl group having 1 to 18 carbon atoms can be mentioned. The average carbon number of the alkyl group is preferably 3 to 9, more preferably 3 to 6. The preferred (meth)acrylic acid alkyl ester is butyl acrylate. As monomers (comonomers) constituting the (meth)acrylic acid polymer, in addition to the (meth)acrylic acid alkyl ester, carboxyl-containing monomers, hydroxyl-containing monomers, amide-containing monomers, aromatic ring-containing (meth)acrylic acid esters, heterocyclic vinyl monomers, etc. can also be mentioned. The acrylic adhesive composition can preferably contain a silane coupling agent and / or a crosslinking agent. As a silane coupling agent, for example, an epoxy-containing silane coupling agent can be mentioned. As a crosslinking agent, for example, an isocyanate crosslinking agent and a peroxide crosslinking agent can be mentioned. Furthermore, the acrylic adhesive composition can also contain an antioxidant and / or a conductive agent. The details of the adhesive are described in, for example, Japanese Patent Application Publication No. 2006-183022, Japanese Patent Application Publication No. 2015-199942, Japanese Patent Application Publication No. 2018-053114, Japanese Patent Application Publication No. 2016-190996, and International Publication No. 2018 / 008712, and the descriptions of these publications are incorporated herein by reference.

[0063] The storage modulus of the adhesive at 25°C is preferably 1.0×10 4 Pa~1.0×10 6 Pa, more preferably 1.0×10 4 Pa~1.0×10 5When the storage elastic modulus of the binder is within such a range, interlayer peeling, floating, etc. can be suppressed, and adverse effects on the discharge of ammonium ions can be prevented.

[0064] The creep amount ΔCr of the adhesive at 70°C is, for example, 65 μm or less, 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, and further can be 15 μm or less. The lower limit of the creep amount ΔCr is, for example, 0.5 μm. When the creep amount is within such a range, as in the case of the storage modulus, interlayer peeling or floating can be suppressed, and adverse effects on the discharge of ammonium ions can be prevented. It should be noted that the creep value can be measured, for example, by the following steps: a load of 500 gf is applied vertically downward to an adhesive attached to a stainless steel test plate with a joint surface of 20 mm in length and 20 mm in width while the test plate is fixed. The creep amount (displacement) of the adhesive relative to the test plate is measured at each time point 100 seconds after and 3600 seconds after the start of the load application, and is set as Cr respectively. 100 and Cr 3600 According to the measured Cr 100 and Cr 3600 , through the formula ΔCr=Cr 3600 -Cr 100 The creep amount ΔCr can be calculated.

[0065] The thickness of the pressure-sensitive adhesive layer is preferably 2 μm to 40 μm, more preferably 3 μm to 20 μm, and even more preferably 4 μm to 15 μm.

[0066] B. Polarizing plate with phase difference layer

[0067] As described in item A-1 above, the polarizing plate of the embodiment of the present invention may also be bonded with a phase difference layer by means of an adhesive layer 40 to form a polarizing plate with a phase difference layer. Therefore, the polarizing plate with a phase difference layer may also be included in the embodiment of the present invention. The polarizing plate with a phase difference layer of the embodiment of the present invention can significantly suppress discoloration when applied to an organic EL display device. The phase difference layer typically has a circular polarization function or an elliptical polarization function. The phase difference layer typically exhibits an anomalous dispersion wavelength characteristic and can function as a λ / 4 plate. The phase difference layer can be a stretched film of a resin film, or it can be an orientation solidification layer (liquid crystal orientation solidification layer) of a liquid crystal compound. The phase difference layer is preferably a stretched film of a resin film. When it is such a structure, the intrusion of ammonium ions into the polarizer can be well suppressed. As a representative example of the resin constituting the resin film, polycarbonate resins or polyester carbonate resins can be cited.

[0068] C. Organic EL display device

[0069] The polarizing plate described in the above item A and the polarizing plate with a phase difference layer described in the above item B can be applied to an organic EL display device. Therefore, an organic EL display device including a polarizing plate or a polarizing plate with a phase difference layer is also included in the embodiments of the present invention. The organic EL display device is typically equipped with a polarizing plate or a polarizing plate with a phase difference layer on its visual recognition side. The polarizing plate with a phase difference layer is stacked in a manner that the phase difference layer becomes the organic EL unit side (in a manner that the polarizing plate becomes the visual recognition side). In one embodiment, the organic EL display device has a curved shape (substantially a curved display screen) and / or can be bent or bent. As described above, the inventors of the present invention have discovered a new problem that when a polarizing plate and a polarizing plate with a phase difference layer are applied to an organic EL display device, the polarizing plate and the polarizing plate with a phase difference layer are discolored due to ammonia (substantially ammonium ions) generated by the organic EL panel, and the problem is solved by using the polarizing plate described in the above item A and the polarizing plate with a phase difference layer described in the above item B. That is, in the organic EL display device, the effects of the polarizing plate and the polarizing plate with a retardation layer according to the embodiment of the present invention are remarkable.

[0070] Example

[0071] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples. The measuring methods of various properties are as follows. It should be noted that, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are by weight.

[0072] (1) Thickness

[0073] The thickness of the polarizer was measured using an interference film thickness meter (manufactured by Otsuka Electronics Co., Ltd., product name "MCPD-3000"). In addition, the thickness of the adhesive layer was measured by cutting the polarizing plates of the examples and comparative examples, observing the cross section of the polarizing plates with a scanning electron microscope (manufactured by JEOL Ltd., "JSM7100F"), and measuring the thickness based on the microscope image.

[0074] (2) Single-body transmittance and polarization degree

[0075] For the polarizing plates used in the examples and comparative examples, the single transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc measured using an ultraviolet visible spectrophotometer ("LPF200" manufactured by Otsuka Electronics Co., Ltd.) are respectively used as Ts, Tp, and Tc of the polarizer. These Ts, Tp, and Tc are Y values ​​obtained by measuring the 2-degree field of view (C light source) of JIS Z8701 and correcting the visual sensitivity. Based on the obtained Tp and Tc, the polarization degree P is calculated by the following formula.

[0076] Polarization degree P (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0077] The cross transmittance Tc of the measured wavelength 210 nm was respectively determined using "U4100" manufactured by Hitachi High-Tech Corporation. 210 Find the orthogonal absorbance A 210 , and the orthogonal transmittance Tc at a measured wavelength of 550 nm 550 Find the orthogonal absorbance A 550 In addition, the orthogonal transmittance Tc at a wavelength of 470 nm was measured using the product name "V-7100" manufactured by JASCO Corporation. 470 Find the orthogonal absorbance A 470 , and the orthogonal transmittance Tc at a measured wavelength of 600 nm 600 Find the orthogonal absorbance A 600 .

[0078] (3) Moisture permeability

[0079] The measurement was performed in accordance with JIS Z 0208. Specifically, the protective layer (film constituting the protective layer) used in the examples and comparative examples was cut into a 10 cm Φ circle as a measurement sample. The moisture permeability of the measurement sample was measured under the test conditions of 40°C and 92% RH using "MOCON" manufactured by Hitachi, Ltd.

[0080] (4) Orthogonal b value

[0081] The polarizing plates used in the examples and comparative examples were measured using an ultraviolet visible spectrophotometer (manufactured by JASCO Corporation, product name "V7100") to determine the hue in the crossed polarization state. The lower the crossed b value (negative value and large absolute value), the more blue the hue displayed is rather than neutral.

[0082] (5) Ammonia decolorization test

[0083] Place 1.5 ml of 10% ammonia solution in a glass bottle (cylindrical with a diameter of 30 mm and a depth of 50 mm). At this time, the distance from the liquid surface of the ammonia solution to the mouth (upper end) of the glass bottle is about 30 mm. Cut the polarizing plate obtained in the embodiment and the comparative example into a size of 30 mm × 30 mm as a measurement sample. Make the measurement sample cover the entire mouth of the glass bottle, and do not let the steam leak from the gap, and stick the measurement sample to the edge of the glass bottle mouth with the help of an adhesive layer. Heat the glass bottle covered with the measurement sample at 60°C for 2 hours. The polarization degree of the polarizing plate (essentially a polarizer) before heating is set to P0, and the polarization degree after heating is set to P 20 The absolute value of the change in polarization degree |ΔP| is calculated according to the following formula. The smaller |ΔP| is, the more the discoloration caused by ammonia is suppressed.

[0084] |ΔP|=|P20 -P0|

[0085] Based on the obtained ΔP, evaluation was performed according to the following criteria.

[0086] A: |ΔP| is less than 10%

[0087] B: |ΔP| is greater than 10% and less than 25%

[0088] C: |ΔP| is greater than 25% and less than 50%

[0089] D: |ΔP| is greater than 50% and less than 75%

[0090] E: |ΔP| greater than 75%

[0091] [Example 1]

[0092] 1. Production of polarizer

[0093] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.

[0094] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting product was dissolved in water to prepare a PVA aqueous solution (coating liquid).

[0095] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.

[0096] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).

[0097] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0098] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds (dyeing treatment) with a concentration adjusted so that the single body transmittance (Ts) of the final polarizer would be 43.0%.

[0099] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0100] Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, and uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different circumferential speeds so that the total stretching ratio became 5.5 times.

[0101] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by adding 3 parts by weight of potassium iodide to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).

[0102] Thereafter, the film was dried in an oven maintained at about 90° C., and brought into contact with a SUS heating roll maintained at a surface temperature of about 75° C. (drying shrinkage treatment).

[0103] In this way, a polarizer is formed on the resin substrate, and a laminate having a structure of resin substrate / polarizer is obtained.

[0104] 2. Production of polarizing plate

[0105] The protective layer is bonded to the surface of the polarizer of the laminate obtained above with the aid of an adhesive layer. The details are as follows. 6.02 parts of acetoacetyl-modified PVA (polymerization degree 1200, acetoacetyl modification degree 4.6%, saponification degree 99.0 mol% or more, solid content concentration 4%, manufactured by Mitsubishi Chemical Corporation, trade name "GOHSENX Z-200"), 25 parts of an aqueous solution containing positively charged alumina colloid (average particle size 15 nm) at a solid content concentration of 3.2%, and 18.98 parts of pure water are mixed to obtain a water-based adhesive. The resin composition is applied to the surface of the polarizer in such a manner that the thickness after drying becomes 0.09 μm, and after bonding the HC-TAC film using a roller press, the resin composition is dried to form an adhesive layer, and the polarizer and the protective layer are bonded. It should be noted that the HC-TAC film is a film in which a hard coating (HC) layer (thickness 7 μm) is formed on a triacetylcellulose (TAC) film (thickness 25 μm), and the film is laminated in such a way that the TAC film becomes the polarizer side. The moisture permeability of the HC-TAC film is 427 g / m 2 ·24h. Then, the resin substrate was peeled off, and an acrylic adhesive (thickness 20μm) was placed on the peeled surface to obtain a polarizing plate having a structure of a visual recognition side protective layer (HC-TAC film) / adhesive layer / polarizer / adhesive layer (acrylic adhesive). The polarizer in the obtained polarizing plate had a thickness of 5μm, a single unit transmittance of 43.0%, and an A 550 / A 210 1.44, A470 / A 600 The value of the cross light was 0.94, and the value of the cross light b was -1.58. The obtained polarizing plate was subjected to the evaluation of (5) above. The results are shown in Table 1.

[0106] It should be noted that the acrylic adhesive was prepared as follows. A monomer mixture containing 91 parts of butyl acrylate, 6 parts of acryloylmorpholine, 2.7 parts of acrylic acid and 0.3 parts of 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator and 100 parts of ethyl acetate were added to 100 parts of the monomer mixture, and nitrogen was introduced while slowly stirring to perform nitrogen substitution. The liquid temperature in the flask was maintained at about 55°C, and a polymerization reaction was performed for 8 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2.7 million and Mw / Mn=3.8. With respect to 100 parts of the solid content of the above acrylic polymer solution, 0.1 parts of trimethylolpropane / toluene diisocyanate adduct (manufactured by Tosoh Corporation, trade name "CORONATE L"), 0.3 parts of a peroxide crosslinking agent (manufactured by NOF Corporation, trade name "NYPER BMT"), and 0.2 parts of an epoxy-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM-403") were added to obtain an acrylic adhesive.

[0107] [Example 2]

[0108] A polarizing plate was obtained in the same manner as in Example 1 except that the thickness of the adhesive layer was changed to 0.07 μm. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0109] [Example 3]

[0110] A polarizing plate was obtained in the same manner as in Example 1 except that the thickness of the adhesive layer was changed to 0.05 μm. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0111] [Example 4]

[0112] A polarizing plate was obtained in the same manner as in Example 1 except that the thickness of the TAC film was changed to 40 μm. The moisture permeability of the TAC film was 300 g / m 2 The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0113] [Example 5]

[0114] The same operation as in Example 1 was carried out except that the stretching conditions were changed to change the optical properties of the polarizer, thereby obtaining a laminate having a structure of a resin substrate / polarizer. The thickness of the polarizer was 5 μm, the single unit transmittance was 43.0%, and the A 550 / A 210 1.37, A 470 / A 600 The following steps were carried out in the same manner as in Example 1 to obtain a polarizing plate. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0115] [Example 6]

[0116] A long roll of a polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, product name "PE3000") with a thickness of 30 μm is uniaxially stretched in the length direction to 5.9 times the length using a roller stretching machine, and is simultaneously subjected to swelling, dyeing, cross-linking, and cleaning treatments, and finally a drying treatment is applied to produce a polarizer with a thickness of 12 μm.

[0117] Specifically, the swelling treatment is to stretch the film to 2.2 times while treating it in pure water at 20°C. Next, in the dyeing treatment, the film is stretched to 1.4 times while treating it in a 30°C aqueous solution with a weight ratio of iodine to potassium iodide of 1:7, in which the iodine concentration is adjusted so that the monomer transmittance of the obtained polarizer becomes 43.0%. Furthermore, in the cross-linking treatment, a two-stage cross-linking treatment is adopted, and the first stage cross-linking treatment is to stretch it to 1.2 times while treating it in an aqueous solution of boric acid and potassium iodide dissolved at 40°C. The boric acid content of the aqueous solution of the first stage cross-linking treatment is 5.0% by weight, and the potassium iodide content is 3.0% by weight. In the second stage cross-linking treatment, the film is stretched to 1.6 times while treating it in an aqueous solution of boric acid and potassium iodide dissolved at 65°C. The boric acid content of the aqueous solution of the second stage cross-linking treatment is 4.3% by weight, and the potassium iodide content is 5.0% by weight. In addition, the cleaning treatment is to treat it in a potassium iodide aqueous solution at 20°C. The potassium iodide content of the aqueous solution in the washing treatment was 2.6 wt %. Finally, in the drying treatment, the polarizer was dried at 70° C. for 5 minutes to obtain a polarizer.

[0118] A polarizing plate was obtained in the same manner as in Example 1 except that the polarizer was used. The thickness of the polarizer was 12 μm, the single body transmittance was 43.0%, and the A 550 / A 210 2.57, A 470 / A 600 The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0119] [Comparative Example 1]

[0120] A polarizing plate was obtained in the same manner as in Example 1 except that the thickness of the adhesive layer was 1 μm. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0121] [Comparative Example 2]

[0122] A polarizing plate was obtained in the same manner as in Example 1 except that an HC-COP film was used as the visual recognition side protective layer instead of the HC-TAC film. The HC-COP film is a film in which a hard coating (HC) layer (thickness 2 μm) is formed on a COP film (thickness 25 μm), and its moisture permeability is 35 g / m 2 · 24 h. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0123] [Table 1]

[0124]

[0125] [evaluate]

[0126] As is clear from Table 1, according to the embodiments of the present invention, it is possible to obtain a polarizing plate whose polarization degree does not substantially change (i.e., does not discolor) even when exposed to ammonia. That is, according to the embodiments of the present invention, it is possible to realize a polarizing plate and a polarizing plate with a phase difference layer in which discoloration is suppressed when applied to an organic EL display device. On the other hand, the polarizing function of the polarizing plate of the comparative example is greatly reduced.

[0127] Industrial Applicability

[0128] The polarizing plate of the present invention is suitable for use in an organic EL display device, and the polarizing plate with a retardation layer is suitable as an antireflection circularly polarizing plate for an organic EL display device.

[0129] Description of Reference Numerals

[0130] 10 polarizers

[0131] 20 Adhesive layer

[0132] 30 protective layers

[0133] 40 Adhesive layer

[0134] 100 polarizing plate

Claims

1. A polarizing plate comprising: a polarizer, a protective layer attached to one surface of the polarizer via an adhesive layer, and an adhesive layer disposed on the other side of the polarizer, The thickness of the adhesive layer is 0.5 μm or less. The moisture permeability of the protective layer according to JIS Z0208 is 330g / m 2 More than 24 hours, and the iodine adsorption per unit area is 0.01mg / cm 2 the following, The thickness of the polarizer is less than 8 μm, the iodine concentration is 4 wt% to 10 wt%, the boric acid concentration is 16 wt% to 26 wt%, and the orthogonal absorbance A at a wavelength of 550 nm is 550 Orthogonal absorbance A at wavelength 210nm 210 A 550 / A 210 The orthogonal absorbance A at a wavelength of 470 nm is 1.4 or more. 470 Orthogonal absorbance A at wavelength 600nm 600 A 470 / A 600 is greater than 0.7, and the orthogonal b value is greater than -10, When the polarizing plate is exposed to ammonia vapor in an environment of 60° C. for 2 hours, an absolute value of a change in polarization degree |ΔP| is 14.9% or less.

2. The polarizing plate according to claim 1, wherein The adhesive layer is composed of a water-based adhesive.

3. The polarizing plate according to claim 2, wherein: The water-based adhesive includes a polyvinyl alcohol-based resin. 4 . A polarizing plate with a retardation layer, comprising the polarizing plate according to claim 1 and a retardation layer. 5 . An organic electroluminescent display device comprising the polarizing plate according to claim 1 or the polarizing plate with a retardation layer according to claim 4 .

Citation Information

Patent Citations

  • Optically active liquid crystal compound having cyano group

    JP1989070455A

  • Protective film for polarizer and its manufacturing method

    JP2001343529A

  • Composite optical retardation plate, circularly polarizing plate and liquid crystal display, organic el display device

    JP2002372622A

  • Apparatus for treating garbage

    JP2003311239A

  • Pressure-sensitive adhesive for optical film, pressure-sensitive adhesive layer for optical film, its manufacturing method, pressure-sensitive adhesive optical film and image display device

    JP2006183022A